THE CURIOSITY EFFECT ON STUDENTS' READING COMPREHENSION - Good Sumbayak Sitopu Lingga (Universitas Pamulang, 2021)
The purpose of this study was to find out whether curriculum has a significant effect on students' reading comprehension or not. This study uses a quantitative ex post facto method. The research instrument used consisted of tests and questionnaires which were distributed to the sample. The population in this study were students of class X from SMA NEGERI 1 BANGUN PURBA (200 students) and the sample of this study was 60 students. The researcher took the sample using proportional stratified sampling technique, in which the sample was divided into three groups proportionally: high, medium, and low curiosity. The results of this study indicate that curriculum has a significant effect on reading comprehension of students in class X. It is shown from the average score of students with high curriculum (83.5) which has a higher score than the average score of students with low curiosity (60). It is also shown from the results of statistical calculations that the value of tp (7.150) > tt (2.086) at the significance level (α = 0.05). From these calculations, the alternative hypothesis is accepted and the null hypothesis is rejected.